2019
DOI: 10.1101/715888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Absolute measurement of the tissue origins of cell-free DNA in the healthy state and following paracetamol overdose

Abstract: AbstractBackgroundDespite the emergence of cell-free DNA (cfDNA) as a clinical biomarker in cancer, the tissue origins of cfDNA in healthy individuals have to date been inferred only by indirect and relative measurement methods, such as tissue-specific methylation and nucleosomal profiling.MethodsWe performed the first direct, absolute measurement of the tissue origins of cfDNA, us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…14,39 Our study revealed an inverse correlation of cfDNA with ALC (r ¼ -0.683; P < 0.001); this was in line with Laurent et al, who stated that haematopoietic cells, including lymphoid and erythroid cells, are the major components of cfDNA. 40 There was a positive correlation of cfDNA with NLR (r ¼ 0.698; P < 0.001), which can be attributed to activation and migration of neutrophils to the bloodstream during COVID-19 and their release of large amounts of ROS which can induce cell DNA damage and release of circulating cfDNA. Likewise, associated lymphopenia due to lymphocyte apoptosis contributes to more release of cfDNA.…”
Section: Aucmentioning
confidence: 92%
“…14,39 Our study revealed an inverse correlation of cfDNA with ALC (r ¼ -0.683; P < 0.001); this was in line with Laurent et al, who stated that haematopoietic cells, including lymphoid and erythroid cells, are the major components of cfDNA. 40 There was a positive correlation of cfDNA with NLR (r ¼ 0.698; P < 0.001), which can be attributed to activation and migration of neutrophils to the bloodstream during COVID-19 and their release of large amounts of ROS which can induce cell DNA damage and release of circulating cfDNA. Likewise, associated lymphopenia due to lymphocyte apoptosis contributes to more release of cfDNA.…”
Section: Aucmentioning
confidence: 92%
“…Thus, the 1994 discovery of a KRAS p.G12D point mutation in ccfDNA derived from pancreatic cancer was a landmark occasion because the detection of tumour-derived ccfDNA (circulating tumour DNA [ctDNA]) provided incontrovertible molecular proof for the viability of the non-invasive detection of cancer [12]. Haematopoietic cells account for > 90% of the ccfDNA in healthy individuals [13][14][15][16]. The remaining portion of ccfDNA is principally derived from endothelial cells and hepatocytes [13,14,16].…”
Section: Why Is the Fragment Length Of Circulatingmentioning
confidence: 99%
“…Haematopoietic cells account for > 90% of the ccfDNA in healthy individuals [13][14][15][16]. The remaining portion of ccfDNA is principally derived from endothelial cells and hepatocytes [13,14,16]. In the presence of solid tumours, the proportion of ccfDNA composed of ctDNA is generally Advancing cell-free DNA diagnostics to early-stage and non-metastatic cancers has been limited by challenges associated with distinguishing the true signal of lowfrequency tumour-derived cell-free DNA from noise generated during next-generation sequencing.…”
Section: Why Is the Fragment Length Of Circulatingmentioning
confidence: 99%
“…When a cell dies, DNA is released into the bloodstream in short fragments (approximately 160bp, the length of a nucleosome) [7]. All people are thought to have a low level of cfDNA in their blood [8] [9]. In healthy individuals, cfDNA in the blood likely arises from normal cell turnover.…”
Section: Introductionmentioning
confidence: 99%